Imaging of pediatric great vessel stents: Computed tomography or magnetic resonance imaging? - A M den Harder; D Suchá; R W van Hamersvelt; R P J Budde; P A de Jong; A M R Schilham; C Bos; J M P J Breur; T Leiner (PLoS ONE, 2017)
Background Complications might occur after great vessel stent implantation in children. Therefore follow-up using imaging is warranted. Purpose To determine the optimal imaging modality for the assessment of stents used to treat great vessel obstructions in children. Material and methods Five different large vessel stents were evaluated in an in-vitro setting. All stents were expanded to the maximal vendor recommended diameter (20mm; n = 4 or 10mm; n = 1), placed in an anthropomorphic chest phantom and imaged with a 256-slice CT-scanner. MRI images were acquired at 1.5T using a multi-slice T2-weighted turbo spin echo, an RF-spoiled three-dimensional T1-weighted Fast Field Echo and a balanced turbo field echo 3D sequence. Two blinded observers assessed stent lumen visibility (measured diameter/true diameter *100%) in the center and at the outlets of the stent. Reproducibility of diameter measurements was evaluated using the intraclass correlation coefficient for reliability and 95% limits of agreement for agreement analysis. Results Median stent lumen visibility was 88 (IQR 86-90)% with CT for all stents at both the center and outlets. With MRI, the T2-weighted turbo spin echo sequence was preferred which resulted in 82 (78-84%) stent lumen visibility. Interobserver reliability and agreement was good for both CT (ICC 0.997, mean difference -0.51 [-1.07-0.05] mm) and MRI measurements (ICC 0.951, mean difference -0.05 [-2.52 --2.41] mm). Conclusion Good in-stent lumen visibility was achievable in this in-vitro study with both CT and MRI in different great vessel stents. Overall reliability was good with clinical acceptable limits of agreement for both CT and MRI. However, common conditions such as in-stent stenosis and associated aneurysms were not tested in this in-vitro study, limiting the value of the in-vitro study.